Pengaruh Social Media Marketing dan Online Customer Review terhadap Minat Beli Produk Liptint Hanasui pada Siswi SMAN 12 Medan - Afriyati, Try Raras; Royani, Ida (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Social Media Marketing and Online Customer Reviews on the Purchase Interest of Hanasui Lip Tint Products among Female Students at SMAN 12 Medan. The research approach used is quantitative, which will determine the extent of the influence of independent variables on dependent variables. The population in this study consists of 611 female students at SMAN 12 Medan, and the sampling technique uses the Slovin formula, resulting in a sample size of 85 respondents. Data analysis was conducted using SPSS with multiple linear regression analysis to determine the influence of independent variables on the dependent variable. The results of the study indicate that the Social Media Marketing variable has a positive and significant influence on the purchase interest in Hanasui Liptint products. This is evident from the significant value (0.000) < 0.05 and the beta value of 0.408. The Online Customer Review variable has a positive and significant influence on the purchase interest in Hanasui Liptint products. This is evident from the significant value (0.000) < 0.05 and beta value of 0.436. Online Customer Review has a more dominant influence than Social Media Marketing in influencing the purchase intention of Hanasui Liptint products among female students at SMAN 12 Medan. Simultaneously, Social Media Marketing (X1) and Online Customer Review (X2) together significantly influence the purchase intention of Hanasui Liptint products among female students at SMAN 12 Medan.